MODERATING EFFECT OF PERSONALITY TRAITS ON THE INFLUENCE OF ISLAMIC FINANCIAL LITERACY ON THE IMPLEMENTATION OF ISLAMIC FINANCIAL PLANNING - Rahmanita, Nadya Dwi; Kusnendi, Kusnendi; Utami, Suci Aprilliani (Fakultas Pendidikan Ekonomi dan Bisnis, 2020)
Abstract. Islamic financial planning is a realization in applying maqashid sharia in terms of improving the welfare of an individual in relation to preserving faith, self, sense, posterity and wealth. This study aims to determine the effect of Islamic financial literacy reinforced by personality traits in the implementation of Islamic financial planning. This study uses purposive sampling - judgment sampling method with 138 respondents. This study also uses survey method with explanatory approach. The results of this study indicate that Islamic financial literacy has a significant predictor for Implementation of Islamic financial planning, after that conscientiousness and neuroticism have a significant effect on the relation of Islamic financial literacy with the implementation of Islamic financial planning, but other personality traits such as extroversion, agreeableness, and opennes to experience do not have significant effect on the relation of Islamic financial literacy with the implementation of Islamic financial planning.Â Â Keyword. Islamic financial planning, Islamic financial literacy, personality traits